2016
DOI: 10.1002/pc.24257
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wood plastic composite based on HDPE and cashew nutshells processed in a thermokinetic mixer

Abstract: Wood plastic composites (WPC), which are used in high-value markets, contribute to solve some of the problems associated with municipal solid waste accumulation. In this study, the effect of cashew nutshell powder (CNSP) content on properties of formulations with recycled high-density polyethylene, 5 wt% of maleic anhydride grafted polypropylene and 5 wt% of struktol TPW 113, a blend of complex, modified fatty acid ester, was evaluated. Mixtures containing from 20 to 60 wt% CNSP were melt-processed, using a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…2 and 3, increases in the MAPP content results in a decline in the composite melts' complex viscosities for both 10% and 30% WF contents. This observation aligns with findings from previous studies, where researchers have consistently reported a reduction in composite viscosity attributed to the plasticizing effect of MAPP [18][19][20][21]. The plasticizing effect of MAPP can be attributed to its higher Melt Flow Index (MFI), which inherently enhances the flow behaviour of the matrix.…”
Section: Complex Viscosity Of Wpcsupporting
confidence: 91%
See 1 more Smart Citation
“…2 and 3, increases in the MAPP content results in a decline in the composite melts' complex viscosities for both 10% and 30% WF contents. This observation aligns with findings from previous studies, where researchers have consistently reported a reduction in composite viscosity attributed to the plasticizing effect of MAPP [18][19][20][21]. The plasticizing effect of MAPP can be attributed to its higher Melt Flow Index (MFI), which inherently enhances the flow behaviour of the matrix.…”
Section: Complex Viscosity Of Wpcsupporting
confidence: 91%
“…In contrast, the inclusion of MAPP resulted in an increase in strain due to its plasticizing effect. As aforementioned, the MAPP coupling agent migrates to the matrix-WF interphase, where it enhances adhesion [21, 23,25]. However, owing to its plasticizing effect, it facilitates WF wetting, thereby improving flowability upon shear stress application.…”
Section: Creep Behaviour Of Melt Compositesmentioning
confidence: 99%
“…Researchers explored the use of polymeric matrices to create composites with CNS. Gomes et al (2018) combined CNSP with a recycled high-density polyethylene (rrHDPE) matrix to develop Wood Plastic Composites. Different CNS concentrations were investigated, and the composite properties were evaluated.…”
Section: Compositesmentioning
confidence: 99%
“…The results indicated that MFI played an important role not only in the mechanical properties of the matrix itself but also in the wettability between the particles and the matrix. Gomes et al [ 13 , 14 ] also reported that the higher the MFI, the poorer the tensile and impact strengths of the matrix, but the better the mixture and process conditions. Fu [ 9 ] reported that a lower-MFI matrix usually led to a strong interaction between the fibers and the matrix, resulting in a lower mean fiber length; therefore, the fiber-reinforcing efficiency of the composite decreased.…”
Section: Introductionmentioning
confidence: 99%